Senegal : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
In Senegal, average annual real GDP growth has been more than 5 percent since 1995, with inflation well below 3 percent. Senegal's economic performance has been broadly satisfactory in 2000 and during the first quarter of 2001. Yet, despite this economic performance, poverty is still prevalent. According to the household survey of 1995 Enquete Senegalaise Aupres des Menages (ESAM), 65 percent of the population is below the poverty line. The human development index of the United Nations Development Program (UNDP) ranks Senegal 154th out of 174 countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet